“O trabalho aqui é igual cantiga de passarinho: de segunda a segunda” - mulheres na produção do bolo de arroz em Mato Grosso - Silva, Regiane Caldeira da (Universidade Federal de São Carlos, 2020)
Through using food as a way of reading and understanding diferent angles of society, the rice cake was selected. From the point of view of production, this research has revealed that the rice cake, a typical dish of Mato Grosso State is often a work carried out by women. Rice and cassava make up the material base of the cake. Other ingredients are added depending on the knowledge and taste of those who produce it. Memory, orality and tradition make up its immaterial basis. The purpose of this study was to explore aspects that go beyond the popularity and glamor of rice cake as a typical dish of Mato Grosso State and sought to identify individuals, translate actions, meanings and relationships, often invisible, that intertwine in the construction of this identity element and the very life. Through interviews, observations, photographic records, bibliographic research and online media, there were found to be many diverse methods in which the rice cake is produced within this region. Production is driven by various motivations, the most significant being family economics. The knowledge, highlighted in the case studies, is traditionally shared among women. With such a wide range of traditions and practises, each producer adopts their own specific form of production, tempering the delicacy with its own history, knowledge, memories, beliefs, and interests, making it unique. This know-how continues to be passed on, especially through orality tradition. Other methods of sharing, however, are gaining momentum, especially with the advent of social media and other online platforms. This study has presented a way in which to identify and understand the more diverse styles of living which are not always revealed to the untrained eye. The difficult and often undervalued nature of this work, as highlighted in this study, shows how the rice cake provides opportunities to identify very ordinary people in everyday life and allows you to visualise that meaning, from a different perspective. These daily activities reveal the basic building blocks of society, as expected.
“The work here is like bird singing: from monday to monday” - women in the production of rice cake in Mato Grosso state
Keywords: Comida típica; Bolo de arroz em Mato Grosso; Mulher; Trabalho; Identidades; Typical food; Rice cake in Mato Grosso State; Woman; Work; Identities; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS